Country food sharing networks, household structure, and implications for understanding food insecurity in Arctic Canada. Issue 1 (2nd January 2016) - Collings, Peter; Marten, Meredith G.; Pearce, Tristan; Young, Alyson G.
ABSTRACT: We examine the cultural context of food insecurity among Inuit in Ulukhaktok, Northwest Territories, Canada. An analysis of the social network of country food exchanges among 122 households in the settlement reveals that a household's betweenness centrality—a measure of brokerage—in the country food network is predicted by the age of the household. The households of married couples were better positioned within the sharing network than were the households of single females or single males. Households with an active hunter or elder were also better positioned in the network. The households of single men and women appear to experience limited access to country food, a considerable problem given the increasing number of single-adult households over time. We conclude that the differences between how single women and single men experience constrained access to country foods may partially account for previous findings that single women in arctic settlements appear to be at particular risk for food insecurity.